2003
DOI: 10.1159/000072147
|View full text |Cite
|
Sign up to set email alerts
|

Lens Epithelial Cell Migration between Posterior Capsule and Intraocular Lens with Variously Finished Posterior Optic Edge and Two Haptic Angulations

Abstract: Purpose: To compare lens epithelial cell migration between intraocular lens (IOL) optics and the posterior capsule of IOLs with various edges and haptic angulations. Methods: Experimental acrylic IOLs with 3 types of finishing (none, polishing, tumbling and polishing) and 2 types of haptic angulation (10 and 15°) as well as 3 (AcrySof® MA30BA, Sensar® AR40, CeeOn® 911) clinically implanted IOLs were inserted in rabbit eyes. Scanning electron-microscopic examination of IOLs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…PCO occurs when residual LECs migrate onto the previously cell-free posterior capsule, in response to the surgical trauma and implantation of an IOL, Fig. 1 [63]. In a further rabbit study by Nishi et al no differences were seen in PCO rates when comparing two square edge design IOLs, the hydrophobic acrylic IOL (Alcon AcrySof Ò MA60BM) and the 3-piece silicone IOL (Pharmacia CeeOnTM 911) [64].…”
Section: Cornea and Conjunctivamentioning
confidence: 99%
“…PCO occurs when residual LECs migrate onto the previously cell-free posterior capsule, in response to the surgical trauma and implantation of an IOL, Fig. 1 [63]. In a further rabbit study by Nishi et al no differences were seen in PCO rates when comparing two square edge design IOLs, the hydrophobic acrylic IOL (Alcon AcrySof Ò MA60BM) and the 3-piece silicone IOL (Pharmacia CeeOnTM 911) [64].…”
Section: Cornea and Conjunctivamentioning
confidence: 99%
“…In addition to the optic edge, it has been observed that the haptic angulation also reduces the incidence of PCO by inducing a pressure gradient over the posterior capsule (111).…”
Section: Iol Designmentioning
confidence: 99%
“…One approach has been to use the IOL design to physically impede the migration of residual LEC along the posterior wall of the lens capsule 3. AcrySof, an acrylate IOL (Alcon), and CeeOn Edge, a silicone IOL (Pharmacia), have sharp optic edges designed to exert contact pressure on the posterior capsule when they unfold, and this has been shown to lower the incidence of PCO clinically 4–10. A second approach involves modification of the chemistry of the IOL material to prevent the adhesion and proliferation of LEC.…”
Section: Introductionmentioning
confidence: 99%